The impact of flexible working arrangements on job satisfaction among employees in shared service centers in Malaysia. - Maha Lakshmi, Nantha Gopalan (2025)
This research examined the influence of flexible work arrangements on employee job satisfaction within shared services organizations in Malaysia. Specifically, it investigated four types of flexible arrangements: flexi-time schedules, compressed workweeks, remote working (WFH), and job sharing. A quantitative research design was employed, utilizing a self-administered questionnaire to collect data from 246 employees based in Kuala Lumpur. Correlation and regression analyses revealed that flexi-time schedules, remote working, and job sharing significantly positively impacted job satisfaction. At the same time, compressed workweeks did not show a statistically significant effect. The findings highlight that flexible and remote work hours are particularly effective in enhancing employee satisfaction in shared services. The study suggests that organizations should adopt these arrangements to promote employee engagement, work-life balance, and overall job satisfaction. This research contributes to the existing literature by providing empirical insights into applying flexible work policies within Malaysia's shared services industry.